Analysis Of Independence Law Of Children Born From Rent Of Women In The Study Of Civil Law - Kartini Pandjab; Rusdin Alauddin; Wahda Z Imam (LEGAL BRIEF, 2022)
Ideally in marriage is the fulfillment of the objectives of the marriage itself, one of which is to obtain legal offspring. Children are the most beautiful gift from God Almighty which is highly coveted by all married couples. But in reality today, not all couples can form a family or give birth to children. This can be due to several things, such as a disease that causes a married couple to be unable to produce offspring. This of course can cause despair for married couples who want to have children. Many married couples are willing to do anything to have a child, not even a few of them adopt children. So with such circumstances, a husband and wife's desire arises to perform artificial insemination by borrowing another woman's womb, then after success they will get a baby or child from the artificial insemination. The surrogate mother program with the correct procedures and the uterus being used for economic needs is very unethical. Although this surrogate mother is quite promising in overcoming several cases of infertility, but because this process is still constrained by laws and regulations due to the absence of legal rules that clearly regulate the practice of surrogate mothers, this of course creates legal uncertainty so that the practice of surrogate mothers it is still questionable what its legal status is. The purpose of this study is to examine the Legal Status of Inheritance and Lineage of Surrogate Mothers in the Civil Law Perspective and to analyze the legal protection of children resulting from the practice of Surrogate Mothers in the Civil Law View. This type of research is included in the category of normative legal research, because in its analysis it uses library materials as a source of research data